2017
DOI: 10.12816/0039670
|View full text |Cite
|
Sign up to set email alerts
|

Effect of General Anesthesia versus Spinal Anesthesia in Cesarean Section on Regain of Gastrointestinal Motility

Abstract: Background: cesarean section is a common major hospital surgical procedure performed nowadays. One of the most common postoperative complications is postoperative gastrointestinal paralysis (Ileus) that must be minimized due to its possible serious consequences. Objectives: this study aims to compare the time to regain intestinal motility after general anesthesia versus spinal anesthesia for cesarean section. Methods: this prospective controlled study was carried out at Ain Shams University Maternity Hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
0
1
1
Order By: Relevance
“…The extent of the change in motility is proportional to the length of anesthesia. Contrasts to our findings, Bayoumi et al [9], found no correlation between duration of surgery in both spinal and general anesthesia groups and regain of gastrointestinal motility this because narrow range of difference in the duration between the operations (40-60minute). This agreed with the result of Graber et al [16], found that the length of operation had little or no effect on the duration of colonic stasis.…”
Section: Resultscontrasting
confidence: 99%
“…The extent of the change in motility is proportional to the length of anesthesia. Contrasts to our findings, Bayoumi et al [9], found no correlation between duration of surgery in both spinal and general anesthesia groups and regain of gastrointestinal motility this because narrow range of difference in the duration between the operations (40-60minute). This agreed with the result of Graber et al [16], found that the length of operation had little or no effect on the duration of colonic stasis.…”
Section: Resultscontrasting
confidence: 99%
“…Regarding the postoperative phase, the importance of early postoperative mobilization has already been highlighted by Jovanovich et al [29] and it has also a crucial relevance for childbearing age women to prevent post-surgical adhesion formation, which can be dangerous for future pregnancies [30]. In line with previous studies, patients who underwent RA in our center showed a significant improvement in early postoperative mobilization, early resumption of bowel motility, and early discharge [5, 16, 21, 31]. Another important aspect is the PONV, a discussed topic in literature.…”
Section: Discussionsupporting
confidence: 75%
“…Anastesi regional terbukti mampu meningkatkan pemulihan aktivitas usus lebih baik dibandingkan anastesi general, dan menurunkan lama rawat inap pasien post pembedahan. Hal ini disebabkan berkurangnya penggunaan opioid post pembedahan dengan anastesi regional (Bayoumi, 2017). Walaupun terbukti lebih aman bagi pasien, hipomotilitas usus masih mampu terjadi pada pasien yang menjalani anestesi regional, jika pembedahan dilakukan pada abdomen dan terjadi manipulasi pada usus.…”
Section: Pembahasan 1 Pengaruh Mobilisasi Dini Terhadap Pemulihan Peunclassified